Poor Household Participation in Payments for Environmental Services: Lessons from the Silvopastoral Project in Quindio, Colombia - Pagiola, Stefano; Rios, Ana R.; Arcenas, Agustin (2012)
As the use of Payments for Environmental Services (PES) approaches in developing countries has grown, concern has arisen over the ability of poorer households to participate. This paper uses data from a PES project implemented in Quindio, Colombia, to examine the extent to which poorer households that are eligible to participate are in fact able to do so. The project provides a strong test of the ability of poorer households to participate in a PES program as it required participants to make substantial and complex land use changes. The results show that poorer households are in fact able to participate at levels that are broadly similar to those of better-off households. Moreover, their participation was not limited to the simpler, least expensive options. Transaction costs may be greater obstacles to the participation of poorer households than household-specific constraints.